ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN LISTRIK UNTUK PERENCANAAN DAN PENGENDALIAN BISNIS DI PT. PLN (PERSERO) CABANG MANADO SELATAN - Mailakay, Dian Christin; Sabijono, Harijanto; Wokas, Heince R. N (Universitas Sam Ratulangi, 2019)
Every company always needs a sales accounting information system because sales are a major activity in the company. A good sales accounting information system must be accompanied by effective business planning and control. With the existence of business planning and control in the company PT.PLN can make the company more focused in conducting the electricity sales process to get profit. The research aims to analyze the electricity sales accounting information system for business planning and control at PT. PLN (Persero) Branch of South Manado whether it has been effective or not. The method used in this research is descriptive analysis with a qualitative approach. The data taken in this study is the report on the results of electricity sales in January-December 2018. The electricity sales information system from planning to being realized has been effective then it can be concluded that the electricity sales accounting information system for business planning and control is running well and has been running well according to company needs.